2014 13th International Conference on Control Automation Robotics &Amp; Vision (ICARCV) 2014
DOI: 10.1109/icarcv.2014.7064582
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory optimization of autonomous driving by differential dynamic programming

Abstract: We present a real-time optimization method for autonomous vehicle motion planning. Trajectory optimization is essential for autonomous vehicle motion planning, due to its non-holonomic motion. Conventional way of optimization is by trajectory smoothing. In this paper, we use differential dynamic programming (DDP) to optimize the trajectory. The key advantage of DDP is that it not only smoothes the trajectory but also considers the non-holonomic constrain of the vehicle. The optimized trajectory is pre-proof to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It was found that the best solution obtained was in the vicinity of a local optimal path. Huang et al (2014), presented a realtime optimization method for AV motion planning using differential dynamic programming. Motion planning includes trajectory generation and trajectory optimization.…”
Section: Path Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the best solution obtained was in the vicinity of a local optimal path. Huang et al (2014), presented a realtime optimization method for AV motion planning using differential dynamic programming. Motion planning includes trajectory generation and trajectory optimization.…”
Section: Path Planningmentioning
confidence: 99%
“…Motion planning includes trajectory generation and trajectory optimization. Conventional methods of optimization involve trajectory smoothing however, Huang et al (2014), decided to integrate differential dynamic programming to solve the optimization problem. The motion planner was tested for obstacle avoidance, however, as this was not the focus of the study the algorithm was not modified with that in mind.…”
Section: Path Planningmentioning
confidence: 99%
“…The differential drive motor control technique has been taken from learning robotics using python as presented in [20]. Paper [21] explains the motion planning of the robot using the differential drive and trajectory smoothing using optimization techniques.Mathematical modeling and behavior of the robot are explained using the skid steering model, the tracking of the robot is also mentioned in paper [22].…”
Section: Related Workmentioning
confidence: 99%
“…This model, as well as similar models, builds a trajectory over time in the form of a differential equation, where it is beneficial to have a small state space describing each point of a trajectory, since the required computational time and space scales with the order n, possibly exponentially (cf. [6], [16], [22]).…”
Section: Introductionmentioning
confidence: 99%